PENANAMAN POHON MANGROVE SEBAGAI AKSI MEMINIMALISIR TERJADINYA BANJIR DAN MENGEMBALIKAN EKOSISTEM LAUT DI DESA PEMENANG BARAT KECEMATAN PEMENANG KABUPATEN LOMBOK UTARA - Ulhaq, Zia; Ningsih, Ade; Inggarnasih, Ningsi; Karlina, Lilis (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
This activity aims to raise public awareness of the benefits of mangrove forests for the people of Teluk Kombal Hamlet. Apart from that, this activity can prevent the rate of abrasion on the coast of Teluk Kombal hamlet. This form of activity is based on a joint movement carried out by students from the Muhammadiyah University of Mataram, representatives of the village disaster agency, representatives from the sub-district head, village officials, youth and community leaders. The method used is the 500 planting awareness movement. The results of the activity have provided a positive response from the community and increased their awareness of the benefits of mangrove forests.